2020
DOI: 10.1017/langcog.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Construals of iconicity: experimental approaches to form–meaning resemblances in language

Abstract: While speculations on form–meaning resemblances in language go back millennia, the experimental study of iconicity is only about a century old. Here we take stock of experimental work on iconicity and present a double special issue with a diverse set of new contributions. We contextualise the work by introducing a typology of approaches to iconicity in language. Some approaches construe iconicity as a discrete property that is either present or absent; others treat it as involving semiotic relationships that c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…However, these speculations require more systematic testing in future studies. On the whole, the fact that different effects were found for different types of iconicity in the present study provides support for the proposal that there are meaningful distinctions between different types of iconicity (Dingemanse et al, 2020).…”
Section: The Role Of Phonology In Iconicity Effects 35supporting
confidence: 84%
See 1 more Smart Citation
“…However, these speculations require more systematic testing in future studies. On the whole, the fact that different effects were found for different types of iconicity in the present study provides support for the proposal that there are meaningful distinctions between different types of iconicity (Dingemanse et al, 2020).…”
Section: The Role Of Phonology In Iconicity Effects 35supporting
confidence: 84%
“…A recent review of the literature suggested three ways in which iconicity can be construed: as a discrete property that is absent or present, as a type of relationship between form and meaning that can come in different kinds, and as a gradient that comes in degrees (Dingemanse, Perlman, & Perniss, 2020). To further investigate the iconicity effect, we adopted the latter two approaches.…”
Section: Construals Of Iconicitymentioning
confidence: 99%
“…Furthermore, iconicity is not a simple property, but comes in different kinds and degrees [34,35]. For example, signs can be more or less iconic, i.e.…”
Section: (I) Motivated Signsmentioning
confidence: 99%
“…A recent approach to the systematic study of iconicity across the lexicons of different languages is to interrogate iconicity ratings in which participants data driven iconicity in asl and english assess the degree of resemblance between the form of a sign or word and its meaning. This method operationalizes iconicity as a substance that comes in degrees (Dingemanse, Perlman, & Perniss, 2020), and in doing so, abstracts away from the particular type of iconic mapping at play. Such aggregation of ratings obscures variability in individuals' subjective assessments of formmeaning pairings, but the advantage of this approach is that it enables analysis of hundreds or thousands of items, allowing systematic study of large swaths of a lexicon (see Winter, 2019).…”
Section: Iconic Affordances Of the Articulatorsmentioning
confidence: 99%